The U–Th–Pb systematics of zircon from the Bishop Tuff: A case study in challenges to high-precision Pb/U geochronology at the millennial scale. (1st November 2015) - Ickert, Ryan B.; Mundil, Roland; Magee, Charles W.; Mulcahy, Sean R.
Abstract: Dating zircon by U–Pb in the Pleistocene Bishop Tuff is challenging because the concentration of radiogenic Pb is low and the correction required for disequilibrium in the intermediate daughter products is large. The dates can be difficult to interpret, because their absolute precision is similar in magnitude to purported timescales of crystallization. Previous estimates of the duration of zircon crystallization span two orders of magnitude and appear to depend on the analytical approach. To reconcile the differing interpretations, we present new SIMS and ID-TIMS zircon Pb/U dates, including some crystals that are dated by both techniques. Both the SIMS and ID-TIMS dates have similar distributions as previous results. Normalized to a Th/Umelt  = 2.81, SIMS spot dates from interior regions of sectioned grains range from 769 ± 31 ka to 845 ± 28 ka (2 σ ) and ID-TIMS dates have a range from 760 ± 7 ka to 793 ± 6 ka. Individual crystals dated by both methods have an average difference of 31 ka, with the SIMS dates being consistently older than the bulk crystal dates. This level of variability precludes the assignment of a geological significance to a mean (or weighted-mean) zircon date. A previous ID-TIMS investigation of single BT zircon that showed apparent statistically significant clustering of zircon ages was compromised by an incorrect treatment of the covariance structure of 230 Th-corrected Pb/U data. We show approximate and exact methods for the correct treatment and demonstrate substantially more scatter in that data than previously recognized. Close scrutiny of available partition coefficient data show that they are not adequately precise for <± 10 ka corrections and even if determined precisely, evidence for disequilibrium uptake of U and Th implies that equilibrium partition coefficients may not be useful. Mismatches between the U–Th systematics of zircon and of glasses suggest that there are gaps in our understanding of the relationship between the two phases, lending uncertainty to the accuracy of disequilibrium corrections that use measured glass compositions. Given these uncertainties in the disequilibrium correction, caution is urged when correcting dates with nominal precisions that are better than ±10 ka. Nevertheless, the youngest zircon ages very likely constrain the eruption age of the Bishop Tuff to <775 ka, which conflicts with some estimates of the 40 Ar– 39 Ar sanidine age of eruption.